ENTROPIYNI PROCESSES IN SOCIO-POLITICAL SYSTEMS - Мислюк, Ю. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In research work the necessity of nonlinear research of the politico-sotsialnih systems within the limits of present institutes and processes is grounded. Entropy processes in the open and closed politico-sotsialnih systems through the second law of thermodynamics are explored. It is specified on interdependence and influencing on entropy of such factors as energy, information, freedom, elections.